Electrophoretic variants of intracellular catalase of different Candida species - Miyasaka, NRS; Unterkircher, C. S.; Carvalho, P. O.; Shimizu, M. T. (Kluwer Academic Publ, 2004)
Intracellular and extracellular catalases of different species of Candida were investigated using different culture media. All the Candida strains produced intracellular catalase, whose enzymatic activity was detected by non-denaturating polyacrylamide gradient (4-30%) gel electrophoresis. The cell extracts presented a major 230 kDa catalase band and in some strains variants of catalase with different molecular weights were detected. Candida catalase activity was not affected by heating at 50degreesC and incubation with beta-mercaptoethanol, but treatment with sodium dodecyl sulphate inhibited or reduced enzymatic activity. Extracellular enzyme activity was not detected in any of the culture filtrate extracts tested.
Keywords: Candida; catalase; electrophoresis; variants; virulence